NEPHROTOXICITY OF GENTAMICIN AND COTRIMOXAZOLE COMBINATION IN RATS - AYÇA, İNCİ BANU (PERGAMON-ELSEVIER SCIENCE LTD, 1994)
1. The nephrotoxicity of gentamicin is well known. However, little information is available regarding the combined effects of gentamicin plus co-trimoxazole (sulfamethoxazole-trimethoprim). Therefore, Wistar rats were treated daily with 100 mg/kg gentamicin or 100 mg/kg gentamicin plus 30 mg/kg trimethoprim-150 mg/kg sulfamethoxazole for 14 days. 2. Serum biochemical parameters were measured on days 0, 8 and 15, and histopathological examinations of kidneys were performed on day 15, one day following end of treatment. Gentamicin treated rats exhibited a 63% increase in blood urea nitrogen (BUN), a 124% increase in uric acid, and a 63% decrease in serum potassium levels on day 15. 3. The combination of gentamicin plus co-trimoxazole partially ameliorated these effects. With the three drug combination no change occurred in BUN, and only a 30% decrease occurred in serum potassium levels. 4. While serum creatinine levels significantly increased following gentamicin, the co-administration of co-trimoxazole resulted in a significant decrease (30%) in creatinine. Histopathological examinations of kidneys suggested a lower degree of nephrotoxicity in rats treated with gentamicin plus co-trimoxazole as compared to animals treated with gentamicin alone. 5. The results support the importance of monitoring serum biochemical parameters when treating with gentamicin or gentamicin plus co-trimoxazole.
Keywords: ACUTE RENAL-FAILURE; AMINOGLYCOSIDE ANTIBIOTICS; TOBRAMYCIN